Turkey's diminishing policy options in Syria. Issue 2 (7th February 2016) - Unknown
Abstract : The increase in the Islamic State's power vis-a-vis the moderate Syrian opposition has reduced Turkey's ability to shape the course of the Syrian conflict in line with its long-term goals of uprooting the Assad regime and expanding its influence in the Middle East. ISIS's rise has also degraded Turkey's domestic security. Ankara currently appears caught between its inability to realise its regional objectives with respect to Syria and its refusal to moderate them, but may soon find political compromise unavoidable.